Photofunctions of iridium(iii) complexes in vesicles: long-lived excited states and visible-light sensitization for hydrogen evolution in aqueous solution. Issue 39 (26th September 2019) - Sebata, Shinogu; Takizawa, Shin-ya; Ikuta, Naoya; Murata, Shigeru
Abstract : Utilization of DPPC vesicles allows water-insoluble photoactive Ir(iii ) complexes to be dispersed in bulk aqueous solution. Abstract : Recently, the photochemistry of cationic bis-cyclometalated Ir(iii ) complexes has gained increasing attention in interdisciplinary studies owing to the characteristic photofunctions of the complexes, including long-lived and strong phosphorescence, visible-light absorption, and photosensitizing properties. Herein, two Ir(iii ) complexes, Ir2 and Ir3, composed of coumarin 6 and different ancillary ligands ( i.e., 4, 4′-dimethyl-2, 2′-bipyridine and 2-(2-pyrazolyl)pyridine) were prepared and characterized to investigate their photophysical properties in several solvents. These compounds were incorporated into DPPC vesicles to investigate their photosensitizing properties in an aqueous solution. Ir2 and Ir3 absorbed light strongly in the visible region and exhibited similar phosphorescence spectral profiles dominated by the coumarin ligands in all tested environments. In contrast, the ancillary ligands and the surrounding environment influenced the excited-state deactivation pathways. For instance, the phosphorescence of Ir2 was weak in highly polar solvents and the vesicle membrane, and in contrast, Ir3 exhibited intense and surprisingly long-lived phosphorescence in these media ( Φ = 25–38% and τ = 32–41 μs). Visible-light illumination of Ir2 and Ir3 bound to the membrane surface resulted in H2 evolution when an electron donor and a water-soluble Ni(ii ) catalyst were present in the outer aqueous phase. Under these conditions, the reaction system incorporating Ir2 performed much better than the Ir3 system in terms of photosensitizer stability and turnover frequency.